Unternehmensgründungen von Ausländern in Deutschland: Einkommenseffekte und Implikationen für die Gründungslehre - Jörn Block; Philipp Sandner; Marcus Wagner; Marc Weiglein (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
– The paper uses data from the German Socio-Economic Panel Study (SOEP) to analyze start-ups by foreigners in Germany. The regression results are the following: First, foreigners in self-employment are found to earn more than foreigners in a regular employment position. Second, foreigners seem to gain more from self-employment relative to Germans. The earnings increase from self-employment is larger for foreigners than it is for Germans. The findings are discussed from a policy and an entrepreneurship education perspective. We argue that there is a great potential for entrepreneurship education targeting foreigners.
Keywords: L26; J15; J30; 330; Self-employment; SOEP; foreigners; Germany; earnings; entrepreneurship education